Analysis of the regulation of electronic land certificates in the Regulation of the Minister of Agrarian and Spatial Planning/Head of the National Land Agency Number 3 of 2023 concerning the Issuance of Electronic Documents - Hidayat, Faishal Amroe; Silvie, Ana Silviana (Jurnal Meta-Yuridis, 2025)
Land certificates is a strong proof of land rights, issued by the State Land Agency of Indonesia. Land certificates contain physical data and juridical data on the land owned. Physical data and Juridical data are stored in the land book at the State Land Agency. Conventional land certificates are issued in the form of books that have been familiar to the community. However, since the issuance of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 3 of 2023 concerning the Issuance of Electronic Documents, conventional land certificates have been converted into electronic land certificates. This study discusses how to regulate electronic land certificates based on applicable laws. The Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 3 of 2023 concerning the Issuance of Electronic Documents regulates the issuance of electronic documents in land registration activities by setting limits on the terms used in its regulation. Using the Normative Juridical research method that seeks to explain electronic land certificates based on the applicable law.